Genomic epidemiology sheds light on the emergence and spread of Mycobacterium bovis Eu2 Clonal Complex in Portugal - André C. Pereira; Ana C. Reis; Mónica V. Cunha (Emerging Microbes and Infections, 2023)
Animal tuberculosis (TB) remains a serious concern for animal and human health. Mycobacterium bovis circulates in multi-host systems, dominated by the European 2 clonal complex (Eu2) in Iberia. In this work, we use genomic epidemiology to infer the emergence, spread, and spatiotemporal patterns of Eu2 in the official epidemiological risk area of animal TB in Portugal. Phylogenetic analysis of 144 M. bovis whole-genome sequences from cattle, wild boar, and red deer, representing the 2002–2021 period, distinguished three Eu2 clades that evolved independently. The major Eu2 clade underwent phylodynamic inferences to estimate the time and location of outbreaks, host transitions, and spatial diffusion as well. The origin of this Eu2 clade was attributed to the red deer population in the Castelo Branco district, near the border with Spain. Most host transitions were intraspecific (80%), while interspecific transmissions between wildlife species (wild boar-red deer), and between wild boar and cattle, were highly supported. Phylogeographic reconstruction evidenced that most transitions (82%) occur within municipalities, highlighting local transmission corridors.Our study indicates that M. bovis continues to spread at the cattle-wildlife interface within the animal TB hotspot area, possibly driven by the foraging behaviour of wild boar near agricultural lands. Red deer seems to be an important driver of TB within wildlife hosts, while the wild boar links the multi-host wildlife community and livestock. This work highlights the value of combining genomic epidemiology with phylodynamic inference to resolve host jumps and spatial patterns of M. bovis, providing real-time clues about points of intervention.